Cellular and mitochondrial taurine depletion in bile duct ligated rats: a justification for taurine supplementation in cholestasis/cirrhosis - Najibi, Asma; Rezaei, Heresh; Kumar Manthari, Ram; Niknahad, Hossein; Jamshidzadeh, Akram; Farshad, Omid; Yan, Feng; Ma, Yanqin; Xu, Dongmei; Tang, Zhongwei; Mehdi Ommati, Mohammad; Heidari, Reza (Clinical and Experimental Hepatology, 2022)
Taurine (TAU) is a free amino acid abundant in the human body. Various physiological roles have been attributed to TAU. At the subcellular level, mitochondria are the primary targets for TAU function. Meanwhile, it has been found that TAU depletion is associated with severe pathologies. Cholestasis is a severe clinical complication that can progress to liver fibrosis, cirrhosis, and hepatic failure. Bile duct ligation (BDL) is a reliable model for assessing cholestasis/cirrhosis and related complications. The current study was designed to investigate the effects of cholestasis/cirrhosis on tissue and mitochondrial TAU reservoirs. Cholestatic rats were monitored (14 and 42 days after BDL surgery), and TAU levels were assessed in various tissues and isolated mitochondria. There was a significant decrease in TAU in the brain, heart, liver, kidney, skeletal muscle, intestine, lung, testis, and ovary of the BDL animals (14 and 42 days after surgery). Mitochondrial levels of TAU were also significantly depleted in BDL animals. Tissue and mitochondrial TAU levels in cirrhotic animals (42 days after the BDL operation) were substantially lower than those in the cholestatic rats (14 days after BDL surgery). These data indicate an essential role for tissue and mitochondrial TAU in preventing organ injury induced by cholestasis/cirrhosis and could justify TAU supplementation for therapeutic purposes.